Consequences of chromosome gain: a new view on trisomy syndromes - Krivega, Maria; Stiefel, Clara M.; Storchová, Zuzana (The American journal of human genetics, 2022)
Chromosome gains are detrimental for the development of the human embryo. As such, autosomal trisomies almost always result in spontaneous abortion, and the rare embryos surviving until live birth suffer from a plethora of pathological defects. There is no treatment currently available to ameliorate the consequences of trisomies, such as Down syndrome (trisomy of chromosome 21). Identifying the source of the phenotypes observed in cells with extra chromosomes is crucial for understanding the underlying molecular causes of trisomy syndromes. Although increased expression of the genes localized on the extra chromosome triggers several pathological phenotypes, an alternative model suggests that global, aneuploidy-associated changes in cellular physiology also contribute to the pathology. Here, we compare the molecular consequences of trisomy syndromes in vivo against engineered cell lines carrying various chromosome gains in vitro. We point out several phenotypes that are shared by variable trisomies and, therefore, might be caused by the presence of an extra chromosome per se, independent of its identity. This alternative view may provide useful insights for understanding Down syndrome pathology and open additional opportunities for diagnostics and treatments.